Resident Stem Cells and Renal Carcinoma - Benedetta Bussolati; Alessia Brossa; Giovanni Camussi (International Journal of Nephrology)
According to the cancer stem cell hypothesis tumors are maintained by a cancer stem cell population which is able to initiate and maintain tumors. Tumor-initiating stem cells display stem or progenitor cell properties such as self-renewal and capacity to re-establish tumors that recapitulate the tumor of origin. In this paper, we discuss data relative to the presence of cancer stem cells in human renal carcinoma and their possible origin from normal resident stem cells. The cancer stem cells identified in human renal carcinomas are not derived from the normal CD133+ progenitors of the kidney, but rather from a more undifferentiated population that retains a mesenchymal phenotype. This population is able to self-renewal, clonogenicity, and in vivo tumor initiation. Moreover, they retain pluripotent differentiation capability, as they can generate not only the epithelial component of the tumor, but also tumor endothelial cells. This suggests that renal cancer stem cells may contribute to the intratumor vasculogenesis.